PERAN PROGRAM CERDAS QUR’AN DALAM MENINGKATKAN KEBERADAAN PADANG TV - Wahyudi, Reski; Rahman, Abdul; Eriswan, Eriswan (Institut Seni Indonesia Padangpanjang, 2024)
Padang TV is one of the local televisions in West Sumatra that has been able to maintain its existence for more than fifteen years. Various challenges are faced by local television in facing competition with local television to national television. Various strategies are carried out to improve its existence, one of which is producing the Cerdas Qur'an program which is produced in the midst of the community. The purpose of this research is to find out how the role of the Cerdas Qur'an program in increasing the existence of Padang TV. The theory used in this research is the strategy of producing television programs, and strategies in attracting audiences in maintaining the existence of Padang TV. The research methodology used in this research is qualitative method and data collection techniques by conducting interviews, observations, and document studies. The results showed that the Cerdas Qur'an Program has a strong role in increasing the existence of Padang TV through several strategies, namely, strategies for producing television programs, strategies for attracting audiences, strategies for producing programs in the community, and utilizing internet media.